A Comparative Analysis of Initiatives and Adaptation Measures To Climate Change Undertaken in Poland and Eastern EU Countries - Michalak, Dorota (Comparative Economic Research. Central and Eastern Europe, 2017)
Climate change is one of the greatest contemporary threats to our planet’s environmental, social and economic condition. It is accompanied by massive changes in life support systems on Earth, where its far‑reaching effects will be felt in the upcoming decades. The development of a national adaptation policy (strategy and/or plan) serves as an instrument that provides the necessary framework for adaptation by coordinating the consideration of climate change across relevant sectors, geographical scales, and levels of decision making. The purpose of this paper is to compare the degree of influence of climate change on the economy of the Eastern European Union and compare national strategies for adaptation to climate change in selected countries of Western Europe and Poland. The study shows that countries bearing the brunt of the negative impacts of climate change are Cyprus, Malta, Bulgaria and Poland. These countries recorded the highest climate change index, the greatest losses in terms of estimated GDP, household welfare, land losses, and lower incomes in the agricultural and tourism sectors. With appropriate adaptation measures, countries such as Lithuania, Latvia and Estonia can take advantage of the future changes in weather conditions. A shift in the productivity of the agricultural sector and tourism from south to north can be noted.